1984
DOI: 10.1159/000118124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Alkaloid (–)-Cathinone on the Release of Radioactivity from Rat Striatal Tissue Prelabelled with <sup>3</sup>H-Serotonin

Abstract: The alkaloid (–)-cathinone, which accounts for the stimulating properties of khat leaves, has a pharmacological profile closely resembling that of (+)-amphetamine. Since amphetamine is known to induce release at CNS serotonin storage sites, experiments were performed to determine whether (–)-cathinone also displays this aspect of amphetamine action. When the effects of (–)-cathinone and (+)-amphetamine on the release of radioactivity from rat striatal tissue prelabelled with 3H-serotonin were compared, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…It is worth noting that certain structural modifications of synthetic AMPH can lead to increased SE activity (Rothman et al, 2001). Work on CATH has also demonstrated similar findings (Kalix, 1984; Nielsen, 1985; Rothman et al, 2003), suggesting that CATH’s effect on increasing synaptic SE availability is present but very weak. In addition, there exist a large body of evidence suggesting that activation of the SE system actually dampens the various stimulatory effects of AMPH and its analogs (Baumann et al, 2011; Breese et al, 1974; Hollister et al, 1976).…”
Section: Amphetamine and Cathinone: Structural And Neurophysiologimentioning
confidence: 58%
“…It is worth noting that certain structural modifications of synthetic AMPH can lead to increased SE activity (Rothman et al, 2001). Work on CATH has also demonstrated similar findings (Kalix, 1984; Nielsen, 1985; Rothman et al, 2003), suggesting that CATH’s effect on increasing synaptic SE availability is present but very weak. In addition, there exist a large body of evidence suggesting that activation of the SE system actually dampens the various stimulatory effects of AMPH and its analogs (Baumann et al, 2011; Breese et al, 1974; Hollister et al, 1976).…”
Section: Amphetamine and Cathinone: Structural And Neurophysiologimentioning
confidence: 58%
“…Indeed, anecdotal reports are consistent in describing the main psychological effects of khat as euphoria, elation, logorrhea, and an alleged increase in concentration, with a consequent improvement in socialization (Halbach, 1972;Kalix, 1984). Reduced fatigue, insomnia, anorexia, and increased libido are also often experienced.…”
Section: Central Nervous System Effects and Dependencementioning
confidence: 93%
“…The acute effects of cathamines (cathinone and cathine) on neurotransmission are basically comparable to those induced by amphetamine: these compounds act by increasing dopamine (DA; Kalix, 1980), serotonin (5-HT; Kalix, 1984), and noradrenaline (NA; Kalix and Braenden, 1985) release. Indeed, similarly to amphetamine, cathinone inhibits the activity of DA, NA, and 5-HT transporters, as observed at synaptic level in the striatum of rats treated with the alkaloid (Fleckenstein et al, 1999;Rothman et al, 2003).…”
Section: Central Neuronal Transmissionmentioning
confidence: 99%
“…In vitro studies, for instance, have shown that cathinone enhances the release of serotonin from the striatum [70,71] and can bind to serotonin receptors [72] . A study by Fleckenstein et al [73] demonstrated serotonin uptake inhibition by cathinone following single or multiple dosing.…”
Section: Khat and Monoaminesmentioning
confidence: 99%